2011
DOI: 10.1007/s12185-011-0962-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic splenectomy for immune thrombocytopenia (ITP) patients with platelet counts lower than 1 × 109/L

Abstract: Laparoscopic splenectomy (LS) has become the gold-standard surgical intervention for the treatment of immune thrombocytopenia (ITP) and the patients who experienced medical relapse to steroid. Fewer series are available regarding LS for patients with an extremely low platelet count. The aim of this study is to investigate the feasibility and safety of laparoscopic splenectomy in the treatment of patients with a preoperative platelet count of less than 1 × 109/L. From April 2006 to Jan 2011, 10 patients were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 17 publications
3
25
0
Order By: Relevance
“…Depending on each study's methodology, the mean operative time was reported as being between 75 and 162 min, (6,7,9,10,13,14,25,44), the mean operative time between 150 and 165 min (17,19) and the median operative time between 109 and 144 min (18,20). However, splenomegaly (7), low platelet count (9), anterior approach (10), indications other than immune thrombocytopenic purpura (ITP) (18,20) and concomitant laparoscopic cholecystectomy (18,20), significantly prolonged the operative time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Depending on each study's methodology, the mean operative time was reported as being between 75 and 162 min, (6,7,9,10,13,14,25,44), the mean operative time between 150 and 165 min (17,19) and the median operative time between 109 and 144 min (18,20). However, splenomegaly (7), low platelet count (9), anterior approach (10), indications other than immune thrombocytopenic purpura (ITP) (18,20) and concomitant laparoscopic cholecystectomy (18,20), significantly prolonged the operative time.…”
Section: Resultsmentioning
confidence: 99%
“…LS can be performed with minimal blood loss (mean 36-60 ml) (6,13,17,19,25) and significantly less blood loss compared to OS (14). In the study of Vecchio et al, platelet transfusion was occasionally required (1 out of 12 patients) (6); in other studies, the need for packed erythrocyte transfusion was rare (9, 10), while intraoperative blood loss of more than 600 ml (9), as well as the anterior approach (10), almost always lead to packed erythrocyte transfusion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since durable remissions have been achieved with splenectomy in patients with chronic refractory ITP [15,16], we planned to perform LS in our patient, which induced a durable remission. We did not administer anti-CD20 monoclonal antibody, since response to this treatment modality can be temporary, and we also had concerns about the long-term immunosuppression and reactivation of viral infections that can be caused by rituximab.…”
Section: Discussionmentioning
confidence: 99%